Health Efficiency Measurement of OECD Countries Against the COVID-19 Pandemic by Using DEA and MCDM Methods - Selamzade, Fuad; Ersoy, Yusuf; Ozdemir, Yahya; Celik, Memet Yusuf (Springer Heidelberg, 2023)
Nowadays, it is seen that the COVID-19 virus has changed with mutation and the most effective method in combating this virus is vaccination. In addition to increasing the number of tests, the development and implementation of policies to increase vaccination rates also increase the efficiency of countries in the fight against the virus. This study aims to measure the efficiency levels of OECD countries in the fight against the COVID-19 pandemic in different periods with data envelopment analysis (DEA). To achieve this goal, efficiency analyses were conducted using the output-oriented DEA-constant return to scale (CRS) model with data for 2021. As a result, Colombia, Denmark, New Zealand, Slovakia, and the USA were efficient, while Slovenia, Hungary, and Chile were the countries with the lowest efficiency scores. For inefficient countries to be efficient in the future, it is suggested that policies should be developed and rapidly implemented to reduce the number of cases and deaths, as well as to increase the number of tests. With the study, it has been concluded that the use of the DEA method together with multi-criteria decision making (MCDM) methods such as TOPSIS, EDAS and CODAS for efficiency evaluation of OECD countries allows for a better ranking of efficient decision-making units.
Keywords: Oecd; Covid-19; Health Efficiency; Dea; Mcdm; Decision-Making Applications; Data Envelopment Analysis; Performance Evaluation; Edas Method; Topsis; Selection; Extension; Determinants; Framework; Airports